Smart Solar–Metal–Air Batteries Based on BiOCl Photocorrosion for Monolithic Solar Energy Conversion and Storage. Issue 7 (7th December 2021) - Lan, Yalin; Batmunkh, Munkhbayar; Li, Peng; Qian, Bingzhi; Bu, Degang; Zhao, Qin; Huang, Hongwei; Sun, Wenping; Zhang, Yu; Ma, Tianyi; Song, Xi‐Ming; Jia, Baohua
Abstract: Herein, a BiOCl hydrogel film electrode featuring excellent photocorrosion and regeneration properties acts as the anode to construct a novel type of smart solar–metal–air batteries (SMABs), which combines the characteristics of solar cells (direct photovoltaic conversion) and metal–air batteries (electric energy storage and release interacting with atmosphere). The cyclic photocorrosion processes between BiOCl (Bi 3+ ) and Bi can simply be achieved by solar light illumination and standing in the dark. Upon illumination, the device takes open‐circuit configuration to charge itself from the sunlight. Notably, in this system, the converted solar energy can be stored in the SMABs without the need of external assistance. In the discharging process in the dark, Bi 0 spontaneously turns back to Bi 3+ producing electrons to induce the oxygen reduction reaction. With an illumination of 15 min, the battery with an electrode area of 1 cm 2 can be continuously discharged for ≈3000 s. Taking elemental Bi as the calculation object, the theoretical capacity of the SMABs is 384.75 mAh g ‐1, showing its potential application in energy storage. This novel type of SMABs is developed based on the unique photocorrosive and self‐oxidation reaction of BiOCl to achieve photochemical energy generation and storage. Abstract : The disc‐shaped bismuth oxychloride, BiOCl, is sensitive to illumination to drive self‐redox (self‐photocorrosion and recovery). Smart new solar–metal–air batteries (SMABs) based on BiOCl hydrogel film electrodes are assembled. The SMABs fully powered by solar energy, can act as an energy storage device with an open circuit voltage of 0.38 V.